ChemInform Abstract: Two‐Step Solid‐State Synthesis of PEPPSI‐Type Compounds. Issue 33 (August 2015) - Adams, Christopher J.; Lusi, Matteo; Mutambi, Emily M.; Orpen, A. Gay
Abstract The two‐step mechanochemical preparation of carbene—pyridine complexes of palladium and platinum is reported.